An Office‐Based Emergencies Course for Third‐Year Dental Students. Issue 8 (24th August 2018) - Wald, David A.; Wang, Alvin; Carroll, Gerry; Trager, Jonathan; Cripe, Jane; Curtis, Michael
Abstract : Although uncommon, medical emergencies do occur in the dental office setting. This article describes the development and implementation of an office‐based emergencies course for third‐year dental students. The course reviews the basic management of selected medical emergencies. Background information is provided that further highlights the importance of proper training to manage medical emergencies in the dental office. Details regarding course development, implementation, logistics, and teaching points are highlighted. The article provides a starting point from which dental educators can modify and adapt this course and its objectives to fit their needs or resources. This is a timely topic that should benefit both dental students and dental educators.